Dispute Settlement Reports 1998. World Trade Organization. (Cambridge University Press, 2000)
The Dispute Settlement Reports of the World Trade Organization (WTO) include Panel and Appellate Body reports, as well as arbitration awards, in disputes concerning the rights and obligations of WTO members under the provisions of the Marrakesh Agreement. These are the WTO authorized and paginated reports in English. An essential addition to the library of all practising and academic trade lawyers, and needed by students worldwide taking courses in international economic or trade law. DSR 1998: IX reports two cases. Firstly, this volume contains Reports of both the Appellate Body and of the Panel in the Guatemalan case about the anti-dumping investigation regarding portland cement from Mexico. Secondly, there is the Award of the Arbitrator in the Indonesian case regarding the automobile industry. The form of citation for this volume recommended by the WTO is DSR 1998: IX.